Probing the multi gap behavior within '11' and '122' families of iron based superconductors: the muon-spin rotation studies. (2nd February 2015) - Khasanov, R; Guguchia, Z
Abstract: Muon-spin rotation ( μ SR) was demonstrated to be a good tool to investigate the temperature and the magnetic field dependence of the superfluid density in the bulk of a superconductor which, within the framework of certain models, allows to determine the energy gap structure as well as to obtain the absolute gap values. In this review paper we present the results of μ SR studies of various compounds belonging to the so called '11' and '122' families of Fe-based high temperature superconductors (Fe-HTSs). The existence of multiple superconducting energy gaps is confirmed by occurence of an inflection point in the temperature dependence of the superfluid density curve. Experiments on the single crystalline samples reveal that the penetration depth anisotropy show an opposite temperature evolution as the upper critical field anisotropy . This resembles the situation in 'architectural' two-gap superconductor MgB2 and confirms the existence of multiple energy gaps in the energy spectra of Fe-HTSs.